Innovation & Creativity Day (AiCD 2021): Abstract Book - UiTM, Pusat Asasi (Pusat Asasi, UiTM Cawangan Dengkil, 2020)
ASASI INNOVATION AND CREATIVITY DAY 2021 is an annual event organized by Innovation, Commercialization, and Industrial Linkage Management Committee, Centre of Foundation Studies with this year’s theme ‘UNLEASHING CREATIVITY, HUMANIZING INNOVATION’. AiCD2021 provides an opportunity for lecturers to be advisors in scaffolding the students’ innovative minds. This will be a platform for the lecturers the importance of innovation culture in their profession.